2018
DOI: 10.1590/1678-4685-gmb-2017-0133
|View full text |Cite
|
Sign up to set email alerts
|

Absence of TERT promoter mutations in colorectal precursor lesions and cancer

Abstract: Hotspot mutations (c.-124bp G > A and c.-146bp G > A) in the promoter region of the TERT gene have been recently described in several types of solid tumors, including glioma, bladder, thyroid, liver and skin neoplasms. However, knowledge with respect to colorectal precursor lesions and cancer is scarce. In the present study we aimed to determine the frequency of hotspot TERT promoter mutations in 145 Brazilian patients, including 103 subjects with precursor lesions and 42 with colorectal carcinomas, and we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…We investigated whether samples in our cohort also harbored somatic mutations at chr5: 1, 295, 228 and chr5: 1, 295, 250 within the TERT promoter, but we found that none of our cancer samples carried these mutations (see Mendeley data). The TERT promoter was also devoid of any somatic single-nucleotide or indel mutations, confirming previous reports that such mutations are of low frequency in colorectal cancer (24,25).…”
Section: Resultssupporting
confidence: 88%
“…We investigated whether samples in our cohort also harbored somatic mutations at chr5: 1, 295, 228 and chr5: 1, 295, 250 within the TERT promoter, but we found that none of our cancer samples carried these mutations (see Mendeley data). The TERT promoter was also devoid of any somatic single-nucleotide or indel mutations, confirming previous reports that such mutations are of low frequency in colorectal cancer (24,25).…”
Section: Resultssupporting
confidence: 88%
“…18 Similarly, these mutations were also not found in Brazilian CRC patients. 32 Besides, TERT promoter mutations were also not found in pheochromocytoma, gastrointestinal and kidney tumors, gastric cancer, colorectal precursor lesions, including tubular adenomas and serrated polyps. 7,33,34 On the other hand, Siraj et al reported TERT promoter mutations, -124C>T and -146C>T, in 13 different cancer types seen in Middle Eastern countries.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, identifying genetic alterations in precursor lesions can lead to molecular-based strategies, improving the sensitivity, specificity, and impact of colorectal screening and surveillance programs. Nevertheless, few studies evaluated the mutation status in South America CRC precursor lesions [ 22 , 23 ]. Results of the first two years (first round) of our colorectal cancer screening program (from Barretos Cancer Hospital program) in Brazil showed a successful implementation with a high test return participation rate, colonoscopy completion, and detection lesion rates.…”
Section: Introductionmentioning
confidence: 99%